(3JWHjb GdefGgL GdLOjOI (B: (3eTcdGJ heSJdReGJ hMdhd ebJQMI ef NdGd CQGA eOjQj GdKGfhjGJ GdQSejI heYdejgGs - (3GdeQcR GdJQHhj ddHMhK hGdGfeGA s ((3HjQhJs (3GdeQcR GdJQHhj ddHMhK hGdEfeGAs, 2003)
(3GdgOa ef gPG GdJbQjQ gh GdJYqQa Ydi GdeTcdGJ GdfGLeI Yf JWHjb GdgjcdjI GdJYdjejI hGdefGgL GdLOjOI hJMOjO eSJdReGJgG hUhdG Edi GbJQGM GdMdhd GdedGFeI; hPdc ef hLgI fXQ CaQGO GdgjFJjf GdEOGQjI hGdJYdjejI aj GdeOGQS hGdKGfhjGJ GdQSejI aj dHfGf(B. (3TedJ GdYjfI (B50% (3ef eOjQj GdKGfhjGJ GdQSejI aj dHfGf ehRYI Ydi GdeMGaXGJ GdSJ Cj MhGdi (B100 (3KGfhjI JTed JYdjeG KGfhjG LRFjG Ch cdjG(B. (3hcGf GdESJHjGf GdCOGI GdhMjOI aj gPg GdOQGSI(B. (3HjfJ GdfJGFL Cf GYJeGO eHOC GdJQajY GdejSQ Ch GdJdbGFj COi Edi JOqf aj eSJhi GdJdGejP hCf JYOO GdehGO bO Tcd EQgGbG ddJdGejP, hCf BdjI GdJQajY hGdJaQjY GdeYJeOI aj GdUaha GdKGfhjI ZjQ ObjbI, hgj JNVY aj CcKQ GdCMjGf deRGLjI GdJdejP hdjS dEecGfGJg hbOQGJg(B. (3hCXgQJ GdfJGFL Cf eMJhi GdefGgL hGdcJH, aj GdeQGMd cGqaI, dG jJhGab aj HYV GdCMjGf eY GdCgOGa, hgh ecKa hdG jJfGSH eY YOO GdMUU GdebQQI dg aj GdefgGL hdG eY bOQI GdJdGejP GdGSJjYGHjI, ceG Cf YedjGJ GdJOQjH Ydi cjajI JWHjb GdefgLjI GdLOjOI de Jcf cGajI, hPdc Ydi eSJhi GdCWQ GdJQHhjI cGaI(B. (3cPdc gfGc fbU aGOM aj YedjGJ GdEYOGO ddeOQHjf GdPjf jbhehf HYedjGJ GdJCgjd hGdJOQjH, hCf GdWQGFb GdfGTWI UYHI GdJWHjb fXQG dVjb GdhbJ GdeNUU dcd MUI, hdcKQI YOO GdJdGejP aj GdUa GdhGMO, hdYOe JhGaQ GdhSGFd GdVQhQjI dJfajPgG(B. (3ceG hCf eYXe GdCHfjI GdeOQSjI ZjQ UGdMI dJWHjb GdefgLjI GdLOjOI, agfGc fbU aGOM aj GdJLgjRGJ hGdhSGFd GdJQHhjI GdVQhQjI(B.s
(3GdfhY (B: (3JbQjQs
Keywords: Compulsory Education; Curricula; Curriculum; Enseignement Obligatoire; Public Sector; Secteur Public; (3GdJYdje GdQSejs; (3GdRGejI GdJYdjes; (3GdefGgLs